2016
DOI: 10.1002/ajh.24416
|View full text |Cite
|
Sign up to set email alerts
|

An international, multicenter, prospective, observational study of neutropenia in patients being treated with lenalidomide + dexamethasone for relapsed or relapsed/refractory multiple myeloma (RR‐MM)

Abstract: Neutropenia is a well‐known dose‐limiting toxicity associated with lenalidomide plus dexamethasone treatment in patients with multiple myeloma; however, little is known about its management and associated outcomes in the real world setting. The present prospective, multicenter, observational study evaluated the incidence, management, and outcomes of grade 3/4 neutropenia in patients with relapsed or relapsed/refractory multiple myeloma who initiated treatment with lenalidomide plus dexamethasone. Of 198 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…The median lowest ANC value was 950 neutrophils/μl (range: 110 to 4320) in patients treated with daratumumab in combination with IMIDs while was 1900 neutrophils/μl (range: 100 to 5700) in patients treated with daratumumab in combination with PIs or as single agent (p-value = 0.003). Indeed, it is well known that IMIDs can cause neutropenia ( 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…The median lowest ANC value was 950 neutrophils/μl (range: 110 to 4320) in patients treated with daratumumab in combination with IMIDs while was 1900 neutrophils/μl (range: 100 to 5700) in patients treated with daratumumab in combination with PIs or as single agent (p-value = 0.003). Indeed, it is well known that IMIDs can cause neutropenia ( 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the observational study by Leleu et al, 31% of patients experienced neutropenia and 23% received G-CSF, which the authors noted was probably reactive. Dose reductions and interruptions with neutropenia as the primary cause were rare [ 42 ]. In the retrospective analysis of patients on the MM-016 extended access programme by Sun et al, intermittent G-CSF (4–6 doses per cycle) was used reactively in 49% of patients and as secondary prophylaxis in 5%.…”
Section: Neutropenia With Current Anti-myeloma Regimensmentioning
confidence: 99%
“…Two of these studies used pegfilgrastim in lenalidomide-based regimens. An observational study of patients with RRMM found that pegfilgrastim was given to 8% of patients receiving RD [ 42 ]. Daily G-CSF was used more frequently (16% of patients).…”
Section: Pegfilgrastim For Neutropenia Prophylaxismentioning
confidence: 99%
See 2 more Smart Citations